Interspecific variation and environmental drivers of rhizosphere microbiomes in endemic Impatiens species - Tang, Zhansheng; Xie, Lina; Chen, Junjie; Wang, Yunquan; Li, Yalei (Frontiers in Plant Science, 2025)
IntroductionUnderstanding rhizosphere microbiomes of endemic plants is crucial for their conservation, yet it remains poorly explored, in particular for species-rich genera with high endemism rates like Impatiens.MethodsWe investigated rhizosphere bacterial and fungal communities of five Impatiens species (including two endemics) across altitude gradients in subtropical China using high-throughput sequencing. We analyzed microbial community structure in relation to environmental factors, soil properties, and plant traits.ResultsSignificant interspecific variations were observed in both bacterial and fungal communities, with endemic species harboring distinct microbiomes. Fungal communities showed stronger species-specificity than bacterial communities, particularly in the endemic I. suichangensis. Redundancy analysis revealed that elevation explained a substantially higher proportion of fungal community variation compared to bacterial variation. Soil nutrients and pH strongly influenced microbial community structure, while plant traits showed species-specific correlations with particular microbial taxa. Notably, companion plant diversity positively correlated with fungal diversity indices.DiscussionThese findings highlight the complex associations among plant traits, environmental factors, and rhizosphere microbiomes in Impatiens species, providing correlative evidence for potential plant-microbe interactions in endemic plant species. Our results emphasize the importance of considering both above- and below-ground components in conservation strategies for endemic plant species.